Modification of Ground-State Chemical Reactivity Via Light–Matter Coherence in Infrared Cavities - Herrera-Urbina, F; Triana-Galvis, J (American Association for the Advancement of Science, 2023)
Reaction-rate modifications for chemical processes due to strong coupling between reactant molecular vibrations and the cavity vacuum have been reported; however, no currently accepted mechanisms explain these observations. In this work, reaction-rate constants were extracted from evolving cavity transmission spectra, revealing resonant suppression of the intracavity reaction rate for alcoholysis of phenyl isocyanate with cyclohexanol. We observed up to an 80% suppression of the rate by tuning cavity modes to be resonant with the reactant isocyanate (NCO) stretch, the product carbonyl (CO) stretch, and cooperative reactant-solvent modes (CH). These results were interpreted using an open quantum system model that predicted resonant modifications of the vibrational distribution of reactants from canonical statistics as a result of light–matter quantum coherences, suggesting links to explore between chemistry and quantum science. Copyright © 2023 the authors, some rights reserved.